2005
DOI: 10.1016/j.pss.2005.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Planar periodic orbits in exterior resonances with Neptune

Abstract: In the framework of the planar restricted three body problem we study a considerable number of resonances associated to the Kuiper Belt dynamics and located between 30 and 48 a.u. Our study is based on the computation of resonant periodic orbits and their stability. Stable periodic orbits are surrounded by regular librations in phase space and in such domains the capture of trans-Neptunian object is possible. All the periodic orbits found are symmetric and there is evidence for the existence of asymmetric ones… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…From this point, we have a bifurcation of the family A A 1 p of asymmetric periodic orbits. Voyatzis and Kotoulas (2005) showed that many families of the external resonances have such critical points and conjectured the bifurcation of asymmetric orbits.…”
Section: The Elliptic Restricted Modelmentioning
confidence: 99%
“…From this point, we have a bifurcation of the family A A 1 p of asymmetric periodic orbits. Voyatzis and Kotoulas (2005) showed that many families of the external resonances have such critical points and conjectured the bifurcation of asymmetric orbits.…”
Section: The Elliptic Restricted Modelmentioning
confidence: 99%
“…As a particular example, the 2/5 resonance is presented in Fig. 1 (a large number of resonances in the Kuiper Belt is studied in Voyatzis & Kotoulas 2005). Fig.…”
Section: Periodic Orbits and Phase‐space Topologymentioning
confidence: 99%
“…3. There are two bifurcation points belonging to the family II and to the family C of circular orbits (for a minor body eccentricity e ≈ 0), each one giving rise to two families of periodic orbits, where the planet is initially at perihelion (family E p ) or at aphelion (family E a ) (see also Voyatzis & Kotoulas 2005). For a particular value of e N (say e N = 0.009), the associated periodic orbits are isolated and they correspond to specific eccentricity values of the small body.…”
Section: Periodic Orbits and Phase‐space Topologymentioning
confidence: 99%
“…For the EKB resonances, the planar circular problem has been extensively studied (Malhotra 1996;Kotoulas & Hadjidemetriou 2002;Voyatzis & Kotoulas 2005b). For all resonances (particularly of first, second and third order), the circular planar RTBP admits two families of symmetric periodic orbits called f amily I and f amily II which bifurcate from the family of circular orbits.…”
Section: Families Of 3d Orbits In the Circular Rtbpmentioning
confidence: 99%
“…For all resonances (particularly of first, second and third order), the circular planar RTBP admits two families of symmetric periodic orbits called f amily I and f amily II which bifurcate from the family of circular orbits. In family I the small body is at perihelion at t = 0, while in family II the small body is at aphelion at t = 0 (for more details, see Voyatzis & Kotoulas 2005b). In Kotoulas & Voyatzis (2005a) The family of circular orbits C in the planar case is not continued near the first order resonances for µ > 0.…”
Section: Families Of 3d Orbits In the Circular Rtbpmentioning
confidence: 99%